Judi Online dan Dampaknya Tehadap Keberfungsian Sosial Keluarga - Fatimah, Sarah Nurul Fatimah; Lia Shafira Arliuanty; Eni Utami (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2025)
The phenomenon of online gambling in Indonesia has shown a significant increase, both in terms of the number of participants and the amount of money in circulation. The adverse impacts of online gambling are increasingly widespread, affecting not only individuals but also families. This study aims to examine the impact of online gambling on family social functioning. A qualitative approach was employed through interviews and observations involving three families affected by online gambling, specifically those in which the head of the household is a former online gambling offender. The findings indicate that involvement in online gambling leads to social dysfunction within the family, manifested in three aspects: (1) the inability to meet basic needs due to economic resources being diverted to gambling activities; (2) the inability to solve problems; and (3) the failure to perform roles according to one’s social status, which disrupts household stability. This study underscores that online gambling is not merely an individual issue, but a broader problem that threatens the stability and social functioning of the family. ABSTRAK Fenomena judi online di Indonesia menunjukkan peningkatan signifikan baik dari jumlah pelaku maupun perputaran uang. Dampak buruk yang ditimbulkan dari kegiatan judi online semakin meluas tidak hanya bagi individu tetapi juga terhadap keluarga. Penelitian ini bertujuan untuk mengkaji dampak judi online terhadap keberfungsian sosial keluarga. Pendekatan kualitatif digunakan melalui teknik wawancara dan observasi terhadap tiga keluarga yang terdampak judi online, yaitu keluarga yang mana kepala keluarganya merupakan eks pelaku judi online. Hasil penelitian menunjukkan bahwa keterlibatan dalam judi online menyebabkan keluarga mengalami disfungsi sosial yang terdiri dari tiga aspek: (1) ketidakmampuan dalam memenuhi kebutuhan karena sumber daya ekonomi digunakan untuk aktivitas judi online; (2) ketidakmampuan menyelesaikan masalah; serta (3) kegagalan dalam menjalankan peran sesuai dengan statusnya, yang mengganggu stabilitas dalam rumah tangga. Studi ini menegaskan bahwa judi online bukan hanya masalah individual, tetapi juga permasalahan yang mengancam stabilitas dan keberfungsian sosial keluarga.